HUBUNGAN KUALITAS PELAYANAN KESEHATAN GIGI DAN MULUT DENGAN TINGKAT KEPUASAN PASIEN DAN DISPARITAS KEPUASAN PASIEN DI PUSKESMAS KABUPATEN PEMALANG - Putri Awwalia Abdul Latif; Hanevi Djasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2023)
Background: Patient satisfaction is one of the key components in various healthcare service parameters as patient feedback can be a measure of healthcare service quality. The rates of oral and dental disease cases are considered high globally, followed by an increased prevalence in Indonesia according to the Basic Health Research from 2007 to 2008, as well as a high rate of self-treatment for dental and oral diseases. Public health centers, as government healthcare service units, require the management to improve the service quality to an optimum level, which is measured by examining the level of patient satisfaction.Objectives: This study aimed to measure the correlation between the quality of dental and oral healthcare services and the level of patient satisfaction at public health centers in Pemalang Regency.Methods: This study is an analytical quantitative study with a cross-sectional approach. A theory proposed by the Institute of Medicine (IOM) stating that healthcare services should pursue six primary goals: patient safety, effectiveness, patient-centeredness, timeliness, efficiency, and equity, was used as a modified design to determine patient satisfaction in dental clinics. The sample size was 212 patients, with 106 patients drawn from each of the two Public Health Centers: Mulyoharjo (urban area) and Bantarbolang (rural area) using the consecutive sampling technique. The data were collected through a survey that involved a questionnaire. Univariate, bivariate, and multivariate analyses were used to analyze the data.Results: Patient characteristics (age, education, occupation, income, and access to healthcare facilities) and the quality of dental and oral health services had a significant correlation with the level of patient satisfaction. The most influential predictor was the quality of dental and oral health services, as indicated by the p-value, with moderate correlation strength. There was a disparity in patient satisfaction between Mulyoharjo Public Health Center (urban area) and Bantarbolang Public Health Center (rural area), where the level of patient satisfaction at Bantarbolang Public Health Center was higher than that at Mulyoharjo Public Health Center.Conclusions: In conclusion, there was a correlation between patient characteristics and the quality of dental and oral health services with the level of patient satisfaction. A disparity in patient satisfaction was found at the dental clinics between Mulyoharjo Public Health Center (urban area) and Bantarbolang Public Health Center (rural area).